INFORMATION-PSYCHOLOGICAL WAR AND TECHNOLOGIES OF SOCIAL ENGINEERING - Yudin, A.; Matviychuk-Yudina, O.; Suprun, O. (Science-based technologies, 2021)
In the article the methods of social engineering, including the use of computer graphics as a key aspect of the psychological impact on human consciousness and one of the possible means of information warfare, a tool for hybrid wars at the interstate level and in business services and financial fraud are discussed and compared. The international experience of social engineering techniques and technologies in information technologies are analyzed. Peculiarities of realization of social engineering tools on the basis of information and communication technologies are determined. Examples of the use of basic technologies of social engineering are given.